Solar Powered Automated Irrigation System in Rural Area and their Socio Economic and Environmental Impact - Tamoor, Muhammad; ZakaUllah, Paris; Mobeen, Mehwish; Zaka, Muhammad Ans (International Journal of Sustainable Energy and Environmental Research, 2021)
One of the most important solutions for the climate change crisis is the development of renewable energy sources like photovoltaic energy. This study is conducted to explore the socio economic and environmental impact of using solar powered automated drip irrigation system on drip owners of Faisalabad division. Drip irrigation technology takes into account innovations in the agricultural sector and their acceptance on behalf of farmers due to various factors of its particular adjustment goes back to social, economic and climatic conditions. Solar powered drip irrigation system is a micro irrigation system that saves water (H2O) and nutrients by allowing water to slowly drip to the roots of plants and minimize water evaporation by using indigenous resources like photovoltaic energy. This study focused on powered automated drip irrigation methods that have a significant impact on resource savings like saving in energy, labour cost and less use of water, improve crop yields and farmer profit that help to improve life of the rural areas. A sample of 48 respondents was selected conveniently from the Faisalabad division. Respondents were solar drip adopter. Descriptive and inferential statistical techniques were applied for data analysis to check the impact of solar drip irrigation on farmer. It was found that majority of solar drip owners are highly agreed to have change in their social status and self-reliance that are 39.58% and 72.92%. Using solar drip systems 79.17% farmers improve their product quality. This indicates that most solar drip owners have high socio-economic and environmental impact.